Comparing time focus with time importance for measuring future time perspectives in the context of pro-environmental values and outcomes - Olsen, Svein Ottar; Tuu, Ho Huy; Tudoran, Ana Alina (Frontiers in Psychology, 2023)
In the area of environmental psychology, time and the temporal perspective have often been used as an overarching framework to explain or predict environmental outcomes. This study aims to introduce a new Time Importance Scale (TIS) based on the attitude strength theory and to assess its nomological validity in comparison with the more established Temporal Focus Scale (TFS) in the context of consumers’ willingness to pay more for environmentally friendly products. The new TIS scale is short and simple to manage. This study proposes competing plausible structural models testing alternative relationships between future time perspective (FTP) and environmental values using a nationwide representative survey sample of 633 Norwegians. The results confirm the convergent and discriminant validity of the new TIS scale. However, the direct association between the TIS scale and willingness to pay for environmentally friendly products is weak or non-significant depending on the alternative models used to validate the nomological validity. However, the new TIS scale provides evidence of a possible causal chain, FTP → environmental values → willingness to pay, with solid associations between the present TIS and hedonic values and between the future TIS and biospheric values. Environmental values are activated by FTP. In most cases, the new TIS outperforms the established TFS in nomological validity. Future research should validate our findings in experimental studies to confirm more robust causal relationships.